INVESTIGATION OF MOLECULAR INTERACTION BETWEEN PHENYLACETYLENE AND HEXAMETHYLPHOSPHORIC TRIAMIDE BY 13C NMR T1 RELAXATION TIME STUDIES AND AB INITIO QM CALCULATIONS - Parsaoran Siahaan; Cynthia L. Radiman; Susanto Imam Rahayu; Muhamad A. Martoprawiro; Dieter Ziessow (Indonesian Journal of Chemistry, 2007)
Intermolecular interactions and molecular translational and rotational mobility are key factors in molecular material sciences, e.g. liquid crystals. One of the important substructures is given by phenylacetylene, Ph-CºCH. Its rotational behavior in its pure form and in high dilution in hexamethylphosphoric triamide OP[N(CH3)2]3 (HMPA) has been studied by means 13C NMR T1 relaxation times at ambient temperature as measured by the inversion recovery method. HMPA is an exceptional solvent in that is has a quite large dipole moment but comparatively low relative dielectricity constant. From the molecular shape Ph-CºCH is expected to exhibit anisotropic rotational diffusion which in fact can be deduced from the measured set of T1 values of the ortho, meta and para carbon nuclei in the neat liquid as well as in the HMPA solution. This expected result rules the dominance of a linearly molecules pair Ph-CºCH...HMPA along their dipole moment axes as anticipated in view of the large HMPA dipole moment. In order to conform with the T1 data, a linear arrangement of Ph-CºCH via the interaction between its weakly acidic H-atom with negatively charge O-atom of HMPA molecules seems to lead to such an anisotropic rotational motion. This hypothesis is supported by ab initio QM calculations which come out with higher interaction energy for linear orientation than other geometries. These ab initio calculations were performed with the basis set of RHF/6-31G(d) for the single molecules of Ph-CºCH and HMPA as well as for their various geometries of the molecules pair. Molecular dynamics simulations need to be performed for further confirmation.